2020
DOI: 10.1002/pros.23972
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic profiling of Pten gene‐knockout mouse model of prostate cancer

Abstract: Background The prostate‐specific phosphatase and tensin homolog deleted on chromosome 10 (Pten) gene‐conditional knockout (KO) mouse carcinogenesis model is highly desirable for studies of prostate cancer biology and chemoprevention due to its close resemblance of primary molecular defect and many histopathological features of human prostate cancer including androgen response and disease progression from prostatic intraepithelial neoplasia to invasive adenocarcinoma. Here, we profiled the proteome and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Zhang et al [ 99 ] compared Pten−/− and wt whole prostates of 4 + 4 mice between 12 and 15 weeks (i.e., when tumors were palpable) with the 8-plex iTRAQ approach. Identification of 711 proteins and further analysis of around 100 DEPs revealed significant enrichment of inflammatory and immune pathways, with a predicted significant upstream role for NF-kB.…”
Section: Large-scale Proteomes Of Prostate Cancer Models Provide Mechanistic Insightsmentioning
confidence: 99%
“…Zhang et al [ 99 ] compared Pten−/− and wt whole prostates of 4 + 4 mice between 12 and 15 weeks (i.e., when tumors were palpable) with the 8-plex iTRAQ approach. Identification of 711 proteins and further analysis of around 100 DEPs revealed significant enrichment of inflammatory and immune pathways, with a predicted significant upstream role for NF-kB.…”
Section: Large-scale Proteomes Of Prostate Cancer Models Provide Mechanistic Insightsmentioning
confidence: 99%
“…Specifically, the cytotoxic effect of these compounds could be tested in vivo in 22Rv1 xenografts implanted in nude mice [ 64 ], as a model of PCa with hyperactivation of p-ERK, or in LNCaP or PC-3 xenografted mice, as these cells are PTEN -null and the AKT pathway is highly activated [ 65 ]. Otherwise, the Pten gene-conditional knockout mouse carcinogenesis model is considered highly desirable to study the potential chemopreventive activity of these compounds in PCa [ 66 ]. Alternatively, the Transgenic Adenocarcinoma of the Mouse Prostate (TRAMP) also mimics the natural progression of PCa, developing lesions that range from preneoplastic to metastasis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to detect indolent prostate cancers from those likely to progress is an important unmet clinical need. In a recent example, using a PTEN gene-knockout mouse model of prostate cancer and 8-plex iTRAQ analysis combined with transcriptomics profiling, Zhang et al [ 46 ] found remarkable macromolecular signatures and revealed key pathway nodes, which shed light on the pathological mechanism behind prostate cancer driven by PTEN-loss, hinting at a potential valuable study direction for prostate cancer intervention.…”
Section: Proteomics the Current Statusmentioning
confidence: 99%